Peran mikoriza dalam meningkatkan produktivitas tanaman pertanian di daerah tropis - Ilmiyah, Alifa (Maliki Interdisciplinary Journal, 2024)
Mycorrhiza is a mutualistic symbiosis between fungi and plant roots, which plays an important role in supporting plant growth and productivity, especially in tropical areas that tend to have less fertile soil conditions and certain nutrient deficits. This study aims to identify the benefits of mycorrhiza in increasing nutrient availability, especially phosphorus, improving soil structure, and increasing plant resistance to extreme environmental conditions, such as drought and pathogen attacks. The results of the study showed that mycorrhiza can increase the efficiency of nutrient absorption, thus having a positive impact on agricultural crop productivity. In addition, the application of mycorrhiza can be an alternative to reduce the use of chemical fertilizers, supporting sustainable agriculture in tropical areas. Based on these findings, it is hoped that the use of mycorrhiza can be optimized in tropical agricultural practices to increase productivity and environmental sustainability.